Histories of the Middle East Studies in Middle Eastern Society, Economy and Law in Honor of A.L. Udovitch - Margariti, Roxani Eleni 1969-; Sabra, Adam Abdelhamid 1968-; Sijpesteijn, Petra; Udovitch, Abraham L. (Brill, 2010)
Dedicated to their teacher, Abraham L. Udovitch, his students offer in this volume a chronologically, geographically and thematically wide range of papers united by an emphasis on a close reading of primary sources and the juxtaposition of different genres of narratives